Pressure-driven occlusive flow of a confined red blood cell. Issue 2 (26th October 2015) - Savin, Thierry; Bandi, M. M.; Mahadevan, L.
Abstract : A pre-swollen red blood cell, which is pressure-driven in a narrowing capillary conduit, is observed to occlude the flow. We analyse this phenomena using elasto-hydrodynamic scalings. Abstract : When red blood cells (RBCs) move through narrow capillaries in the microcirculation, they deform as they flow. In pathophysiological processes such as sickle cell disease and malaria, RBC motion and flow are severely restricted. To understand this threshold of occlusion, we use a combination of experiment and theory to study the motion of a single swollen RBC through a narrow glass capillary of varying inner diameter. By tracking the movement of the squeezed cell as it is driven by a controlled pressure drop, we measure the RBC velocity as a function of the pressure gradient as well as the local capillary diameter, and find that the effective blood viscosity in this regime increases with both decreasing RBC velocity and tube radius by following a power-law that depends upon the length of the confined cell. Our observations are consistent with a simple elasto-hydrodynamic model and highlight the role of lateral confinement in the occluded pressure-driven slow flow of soft confined objects.